Psychometric properties of the Italian version of the Climate Change Anxiety Scale - Matteo Innocenti; Gabriele Santarelli; Vanessa Faggi; Giovanni Castellini; Ilenia Manelli; Gisella Magrini; Ferdinando Galassi; Valdo Ricca (Elsevier, 2021)
Climate change is not only affecting our environment, but also negatively impacting mental health globally. While physical health problems caused by climate change have been increasingly studied in medical literature, few studies have investigated mental health problems caused byclimate change. In order to bridge this gap in the literature and assess the psychological impact of climate change, it is crucial to create adequate psychometric tools such as the Climate Change Anxiety Scale (CCAS) developed by Susan Clayton.In this study, 150 Italian adults (67.4% females, and 32.6% males aged 19-76) were recruited online and required to complete CCAS, as well as GAD-7, K-10, NEP, PEBS, PESE/PSSE, and GSE in order to assess the psychometric properties of and validate CCAS in Italy. Patients were retested after three months. Data was collected from January to June 2021. The study used a 13-item version of the CCAS, which was based on the first two factors of Clayton's original scale. Researchers specifically analyzed internal consistency, test-retest reliability, and discriminant validity.Factor structure of CCAS was specifically addressed: a CFA was carried out to analyze the two-factor structure proposed in the original validation study. An EFA was then conducted and it was hypothesized that a single-factor structure could better fit data.Climate Change Anxiety Scale items exhibited reasonably good internal consistency. Test-retest reliability at a three-month evaluation proved to be good. The experience of climate change anxiety proved to be related to anxiety, pro-environmental behaviors, and low perception of self-efficacy.